Iron(II)/copper(I)-mediated stereoselective carbozincation of ynamides. One-pot synthesis of α-allyl-tetrasubstituted-enamides. Issue 25 (22nd June 2017) - Lingua, Hugo; Vibert, François; Mouysset, Dominique; Siri, Didier; Bertrand, Michèle P.; Feray, Laurence
Abstract: The iron(II) chloride- and copper(I) iodide-mediated carbozincation of a panel of substituted ynamides is described in this article. The reaction is totally regio- and stereoselective. Experiments showed that the reaction mediated with Fe(II) was more substrate dependent than the reaction performed with Cu(I). Interestingly, in the presence of allylbromide, stereoselective carboallylation can be achieved for the first time in a one-pot procedure, leading to skipped dienamides. Graphical abstract: